Factors influencing migration among Nepalese nurses. - Baral. Richa (2014)
ABSTRACT: Migration of Health workers is the problem with devastating consequences for society and nation. It leads to huge loss and lack of health workers in the nation of origin. This research entitled on "Factors Influencing Migration among Nepalese Nurses" was carried out to identify the push factors related to migration of Nurses from Nepal to other developed countries. This study was descriptive in nature and carried out via different Social Medias. The data was collected from 67 Nepalese Nurses who have migrated to four main developed countries: Australia, USA, UK and Canada, who actively participated in the study. Self-administered questionnaire in the form of "Googledocs form" was used to collect data from respondents. The study showed that 70.15% of respondents were of 20-29 years of age and 58.21% of respondents have migrated to abroad since 1-3 years. In the study, 38.80% of respondents were from Australia followed by 31.34% from USA, 16.43% from UK and 13.43% from Canada. When the researcher advised respondents to prioritize the major cause of migration by giving 1 to major and 8 to least responsible factor of migration, the study revealed that Personal ambition (Mean: 3.18), Lack of job and career opportunities in Nepal (Mean: 3.57), Economical factors (Mean: 3.2), and Job dissatisfaction (Mean: 4.90) are the main cause of migration among Nepalese Nurses. This study also showed that 55.22% of respondents were not satisfied with their job in Nepal where as 53.74% of respondents are satisfied and 43.28% of respondents are highly satisfied with their job in Abroad. In conclusion, age and personal ambition tends to influence migration whereas better job and career opportunities in Nepal may encourage migrant Nurses to return Nepal. It can also be concluded that lack of modern facilities merely is not only motivating migration among Nepalese nurses.